How good are patients with panic disorder at perceiving their heartbeats? - Ehlers, A; Breuer, P (1996)
Palpitations are among the most common symptoms of panic attacks. The present review addresses the question of whether systematic differences in heartbeat perception exist between patients with panic disorder and control subjects. Paradigms involving the comparison of heartbeat sensations with external signals such as discrimination task have failed to find group differences. Recent improvements in methodology may give clearer results in future studies. The majority of studies using the mental tracking paradigm have shown that panic disorder patients show a better heartbeat perception than controls. Discrepant results are probably related to different instructions and differences in sample characteristics such as the inclusion of patients on medication affecting the cardiovascular system. More accurate heartbeat perception, may, however, be restricted to those patients who show agoraphobic avoidance behavior. It is also conceivable that group differences in the mental tracking paradigm are due to attentional biases or a tendency to interpret weak sensations as heartbeats rather than differences in perceptual sensitivity. More ambulatory studies are needed to test whether the results can be generalized to the patients' natural environment. So far ambulatory studies have established superior heartbeat perception only in the subgroup of panic disorder patients with cardiac neurosis. A 1-year prospective study showed that heartbeat perception as assessed with the mental tracking paradigm predicted maintenance of panic attacks. This supports the clinical significance of the findings. Increased cardiac awareness may increase the probability of anxiety-inducing bodily sensations triggering the vicious cycle of panic. Laboratory and ambulatory monitoring studies showed that panic disorder patients respond with anxiety when they think that their heart rate has accelerated. Increased cardiac awareness may also contribute to the maintenance of the disorder by motivating the patients to avoid situations in which these sensations occur.